中国名营银行问题研究 = A study of the topics of non-state-owned bank in China - 张双想 Zhang, Shuangxiang (2008)
The issue of "non-State-owned bank" (NSOB) is one of the most sensitive hot topics in the current structural reform of the finance sector in China. Through an analytical study of the economic and financial environment, and the legal and regulatory system, in which the opening of NSOB will encounter, both nationally and internationally, this paper puts forward tendentious ideas and proposition regarding the definition and feasibility of NSOB and the necessary legal and regulatory system to be studied and formulated.